Sustaining food security through social capital in agroforestry: a qualitative study from North Luwu, Indonesia - Yusriadi, Yusriadi (Frontiers in Sustainable Food Systems, 2025)
This research explores the close links between social capital and food security in the rural communities of North Luwu Regency, Indonesia, focusing on the valuable insights gained from agroforestry practices. Using a qualitative approach grounded in social capital theory, the study examines how key indicators—social networks, trust, communal values, and participation—significantly influence regional food production. The findings show that strong social networks, which include relationships with neighbors, family, friends, and farmer groups, positively impact trust, cooperation, and farm efficiency. Trust, often passed down through generations of farming knowledge, remains an important factor, although its dynamics are shifting with changing livelihoods and increasing reliance on agroforestry. Communal values, embodied in agroforestry practices, strengthen individual and collective identities among farmers. Finally, participation in agricultural activities remains essential in understanding social capital’s resilience in agroforestry communities, although it is declining among the younger generation. The research highlights the need for targeted interventions to strengthen the social fabric of these rural communities by strengthening networks, fostering trust, preserving communal values, and encouraging active participation. Ultimately, the study provides a clear picture of the close relationship between social capital and food security. It confirms that solid interactions between social structures and agricultural practices are crucial in shaping resilient and sustainable rural communities that meet their food needs.